Protective Effect of Lemon Grass Oil and Citral on Amelioration of Cadmium-induced Nephrotoxicity and Hepatotoxicity - Shaji, Sona; Suja, Rani S.; Raj, Anoop; Samraj, Sujith (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during January to May, 2025 at Department of Veterinary Pharmacology and Toxicology, at College of Veterinary and Animal Sciences, Mannuthy, Kerala, India to study the potential nephro- and hepatoprotective effects of lemongrass oil (LGO) and its active constitutent, citral against cadmium (Cd) induced renal and hepato damage. Thirty-six adult male Sprague Dawley (SD) rats weighing 150–200 g were kept in well-ventilated polypropylene cages under standard laboratory conditions of 12 h/12 h light/dark cycle at 25°C±2°C with 30–70% relative humidity. The experimental rats were divided into six groups of six animals each. Group I received 0.1% Tween 80 and normal saline, and group II received both cadmium chloride (7 mg kg-1 b.wt.) and Tween 80, while groups III to VI received LGO and citral at 45 and 90 mg kg-1 body weight dose levels, respectively, as oral administration for 28 days, along with cadmium chloride treatment. Significantly elevated serum markers of renal and hepatic dysfunction, alongside the altered oxidative stress indicators, were restored in the present study with LGO and citral treatment. Histological examination further confirmed that LGO and citral at both dose levels attenuated Cd-induced structural damage in kidney and liver tissues. Thus, the results were indicative of significant nephroprotective and hepatoprotective potentials of citral and LGO on Cd-induced nephro- and hepatotoxicity, which might be attributed to its antioxidant activity.